MANAGEMENT COMPETENCES IN AN EMERGENCY SITUATION IN PRIMARY CARE: EXPERIENCE OF A NURSING CURRICULUM ORIENTED BY COMPETENCE - Luís Carlos Lopes-Júnior; Mariana Lieka Assega; Michelle Lopes Machado; Milena Flória-Santos; Sueli Moreira Pirolo (Revista Gestão & Saúde, 2013)
This study aimed to report the experience of last year undergraduate nursing students from Brazilian college pioneer in the use of active teaching-learning methods, in emergency care to a patient in primary care. This assistance which was methodologically problematized triggered by health team, comprised of nurse, physician, nursing assistants and community health worker, a reflection on the organization of the work process. To this end, we used permanent education as a tool guided by the Altadir Method Popular Planning, which contributed to the development of management competence of nurse. A team of health identified problems during assistance, analyzed its causes and consequences, and proposed interventions for the management and organization of the work process to qualify this practice. This report can be useful for the design and implementation of a management exercise that aims to problematize the reality, with a view to linking theory and practice.